International human rights, citizenship education, and critical realism (UCL Press, 2016)
Citizenship education invokes dilemmas even for the most committed teachers and students, researchers, and innovators. How can citizenship education advance equity and equal rights within highly unequal schools and societies? How can it support young people to feel they have the competence, confidence, and right to vote and to challenge injustice? How can we be sure international human rights are realities, not merely passing ideologies? This paper argues that rights really exist as expressions of visceral embodied human needs and moral desires that are integral to human relationships. Rights also serve as powerful legal structures that can help to prevent and remedy wrongs, and they work as enduring high standards and aspirations. The paper suggests how critical realism can help educators to resolve dilemmas in theoretical education about rights as knowledge, principles, and mechanisms, and in practical education that enables students to enjoy and exercise their rights and respect those of other people.